Biology Of The Angoumois Grain Moth, Sitotroga Cerealella (Oliver) On Stored Rice Grain In Laboratory Condition - Akter, T; Jahan, M; Bhuiyan, MSI (Journal of the Asiatic Society of Bangladesh, Science, 2013)
The experiment was conducted in the laboratory of the Department of Entomology, Shere- Bangla Agricultural University, Dhaka during the period from May 2009 to April 2010 to study the biology of the Angoumois grain moth, Sitotroga cerealella (Oliver) in Bangladesh. The ovipositional period, incubation period, larval period, pre-pupal period and pupal period of Angoumois grain moth were 3.67 days, 5.5 days, 25.2 days, 3.0 days and 5.0 days, respectively; male and female longevity of moth were 8.0 and10 days, respectively. The lengths of all five larval instars were 1.0 ± 0.00, 2.0 ± 0.02, 4.0 ± 0.06, 5.0 ± 0.03 and 4.0 ± 0.06 mm, and the widths were 0.10 ± 0.0, 0.4 ± 0.0, 0.6 ± 0.01, 0.8 ± 0.02 and 1.0 ± 0.09 mm, respectively. The length and width of the pre-pupa and the pupa were 4.0 ± 0.02, 3.5 ± 0.01 mm and 1.20 ± 0.05, 1.50 ± 0.03 mm respectively. The length of male and female was 11.2 ± 0.09 and 12.07 ± 0.06 mm respectively. J. Asiat. Soc. Bangladesh, Sci. 39(1): 61-67, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16034